PEMEROLEHAN BAHASA INDONESIA PADA ANAK USIA 0-2 TAHUN: KAJIAN PSIKOLINGUISTIK - Hollysa Andini (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research examines the process of acquiring bahasa Indonesia for the 0-2 years old children in term of phonology and morphology. The research was conducted in one housing resort in Rancak city, the district of Praya, central Lombok namely BTN Pujawan Permai. The reason is that because the people living in this housing resort come from variety of places. In collecting data the researcher applied theory of psycholinguistic using field notes and interview the subjects.  The results are as follows: First, phonologically, the 0-2 years old children are still not able to pronounce some phones clearly such as the fricative consonant [r] which they are changed into lateral consonant [l]. Second, morphologically, children are able to use nouns, adjectives, verbs and some simple phrases correctly event their pronunciation is still not very clear.